2018
DOI: 10.1136/bmjopen-2017-018125
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do hospitalised patients receive appropriate CT and MRI scans? Results of a cross-sectional study in Southern Italy

Abstract: ObjectivesThe aim of this study was to assess the frequency of appropriateness of inpatient CT and MRI scans performed in Southern Italy.MethodsThe study was carried out by retrospectively reviewing medical records of adult patients admitted between 1 January and 31 December 2012 in two hospitals. The evaluation of appropriateness was performed according to the American College of Radiology Appropriateness Criteria, which assigns a score between 1 and 9.ResultsEight hundred and fifty-three medical records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The results according to the anatomical area in the first audit showed dramatically more inappropriate examinations for the lumbar spine area (77%) than for other anatomical areas, a great proportion of which should have been performed by an MRI instead. A recent cross-sectional study in Southern Italy [21] revealed that overall 79.4% of CT examinations (596/751) and 83.6% of MRI examinations (310/371) were appropriate, but that only 66.7% of MRI examinations (38/57) concerning spine and extremities were appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The results according to the anatomical area in the first audit showed dramatically more inappropriate examinations for the lumbar spine area (77%) than for other anatomical areas, a great proportion of which should have been performed by an MRI instead. A recent cross-sectional study in Southern Italy [21] revealed that overall 79.4% of CT examinations (596/751) and 83.6% of MRI examinations (310/371) were appropriate, but that only 66.7% of MRI examinations (38/57) concerning spine and extremities were appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…This compares favourably with international studies. [6] Comparing the findings with the 2012 study results in the same facility, these indicate a favourable trend, with an increase of 17.0%. [10] In both studies, scans were ordered on a digital system, with a clinical history, level of requesting physician and existing laboratory results.…”
Section: Discussionmentioning
confidence: 65%
“…Revisiting the results of the 2012 study, [6] in 2018 consultants requested significantly more appropriate scans (p<0.05), while medical officers requested significantly more inappropriate scans (p<0.05) ( Table 1).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations